Recommendations for POCUS Curriculum in Canadian Undergraduate Medical Education: Consensus from the Inaugural Seguin Canadian POCUS Education Conference - Sacha Weill; Daniel Picard; Daniel Kim; Michael Woo (CINQUILL Medical Publishers Inc., 2023)
Point of care ultrasound (POCUS) in Canadian undergraduate medical education (UGME) is limited. To address this paucity, the inaugural Seguin Canadian POCUS Education Conference hosted 14 of the 17 Canadian medical schools to develop a list of recommendations for POCUS education in Canadian UGME. Attending schools were divided into delegations consisting of a pre-clerkship student, a clerkship student and a staff physician. Recommendations were developed via a modified consensus development panel. Delegations submitted school-specific POCUS education summary documents for roundtable discussions, which yielded an initial set of recommendations. These were then summarized in a large group setting and voted upon for adoption with an a priori agreement threshold of 80%. Conference attendees developed 14 recommendations which 87% of participants agreed to adopt. Conference recommendations reflect the opinions of Canadian trainees and POCUS education experts thus serving as a framework for UGME POCUS education in Canada.